Industrial robotics and the global organisation of production - De Backer, Koen (OECD Science, Technology and Industry Working Papers, 2018)
Increased robot use, fuelled by price declines and the increased dexterity of these machines, is expected to affect existing/future production technologies and the organisation of production within GVCs. In order to safeguard their competitiveness in an increasingly digitalised global economy, governments across OECD and emerging economies are implementing a range of policy measures/programmes to support the investment in and use of robotics. This paper assesses the extent to which robotics impact the organisation of production through offshoring and backshoring. The results indicate that the use of industrial robots in developed economies appears to be slowing the offshoring rates, although it is not yet prompting firms to bring jobs back home. However, the effect is very recent, especially in labour-intensive sectors, and not yet apparent in developing countries. The findings suggest the rate of global value chain expansion may be slower than in the past